2015
DOI: 10.3758/s13420-015-0188-8
|View full text |Cite
|
Sign up to set email alerts
|

Training reinforcement rates, resistance to extinction, and the role of context in reinstatement

Abstract: Behavior reduced as a consequence of extinction or intervention can relapse. According to behavioral momentum theory, the extent to which behavior persists and relapses once it has been eliminated depends on the relative training reinforcement rate among discriminative stimuli. In addition, studies of context renewal reveal that relapse depends on the similarity between the training stimulus context and the test stimulus context following disruption by extinction. In the present experiments with pigeons, we ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 50 publications
0
13
0
2
Order By: Relevance
“…These analyses cannot definitively indicate the extent to which contiguous relations between responding and edibles controlled responding during reinstatement tests but they suggest no support for this interpretation for Wade and Hank but some support for Wanda. Previous examinations of the role of response–reinforcer contiguity suggest no role for adventitious reinforcement in reinstatement effects (Miranda‐Dukoski et al, ; Rescorla & Skucy, ).…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…These analyses cannot definitively indicate the extent to which contiguous relations between responding and edibles controlled responding during reinstatement tests but they suggest no support for this interpretation for Wade and Hank but some support for Wanda. Previous examinations of the role of response–reinforcer contiguity suggest no role for adventitious reinforcement in reinstatement effects (Miranda‐Dukoski et al, ; Rescorla & Skucy, ).…”
Section: Resultsmentioning
confidence: 93%
“…First, the removal of response‐independent reinforcers causes an abrupt change in reinforcer availability, causing previously extinguished target responding to resurge (Shahan & Craig, ; Winterbauer & Bouton, ; see Ecott & Critchfield, ; Virues‐Ortega, Iwata, Fahmie, & Harper, , for a discussion of processes contributing to NCR). In addition, the deliveries of response‐independent reinforcers associated with the target response during reinstatement tests serve as discriminative stimuli, causing target responding to reinstate (Franks & Lattal, ; Miranda‐Dukoski et al, ; Ostlund & Balleine, ; Reid, ; Rescorla & Skucy, ; see Baum, , for a relevant discussion). Thus, the present study revealed separate effects of removing alternative reinforcement (resurgence) and the addition of target reinforcers signaling the previous operant learning history (reinstatement) on relapse.…”
Section: Discussionmentioning
confidence: 99%
“…As found in previous studies (e.g., Podlesnik & Bai, ; Podlesnik et al, 2012, ), the extent to which combining stimuli influenced resistance to extinction depended on the availability of an alternative source of reinforcement, again consistent with behavioral momentum theory (see Nevin & Grace, ). Training a target response in the presence of another concurrently available source of reinforcement (i.e., an enhanced stimulus–reinforcer relation) generally increases its resistance to extinction (e.g., Miranda‐Dukoski, Bensemann, & Podlesnik, ; Nevin & Grace, ). The present study showed that combining an alternative stimulus with a target stimulus associated with a richer history of reinforcement (i.e., DRA probe tests) produced greater resistance to extinction of target responding than combining it with a target stimulus associated with a leaner history of reinforcement (i.e., Combined probe tests).…”
Section: Discussionmentioning
confidence: 99%
“…During each session, we arranged three response‐independent hopper presentations during the first presentation of each component. Hopper presentations were arranged at the start of each component and separated by 5‐, 10‐ or 15‐s intervals, selected randomly from a list (see Miranda‐Dukoski et al, in press; Podlesnik & Fleet, ). Thus, we arranged six hopper presentations in each session of reinstatement during Condition A and nine hopper presentations in each session of reinstatement during Condition B.…”
Section: Methodsmentioning
confidence: 99%
“…After almost complete cessation of responding, pigeons were presented with two brief food presentations in each component at the beginning of sessions to assess relapse via a reinstatement operation (e.g., Reid, ). Responding increased in both components, but more relative to baseline response rates in the Rich Component (see also Miranda‐Dukoski, Bensemann, & Podlesnik, in press). The same pattern of results was then replicated using other relapse manipulations, including renewal (see also Berry, Sweeney, & Odum, ) and resurgence paradigms (see also Kuroda, Cançado, & Podlesnik, ; Podlesnik & Shahan, 2010; Thrailkill & Shahan, ).…”
mentioning
confidence: 98%